(untitled) (DIMENSI: Journal of Architecture and Built Environment, 2016)
One way to reduce energy consumption in buildings is to use daylighting. However, daylight can cause visual discomfort in the form of glare. Center of Art, Design, and Language (CADL) Institut Teknologi Bandung is a building that has windows on west and east facades, so the probability of glare occurrence is high. In this research, CADL was optimized so that the percentage of time that Daylight Glare Probability below 0.21 (%DGP<0.21) is more than 50% and spatial daylight autonomy with illuminance 150 lux and 50% (sDA150lux,50%) is more than 30%. In the optimization, vertical blinds, horizontal blinds, and curtains were added. Vertical blinds and horizontal blinds were varied by changing the blade’s opening angle and area covering the windows, while curtains were varied only by changing the area covering the windows. The results show that %DGP<0.21 can be increased beyond 50%, but in some rooms, sDA150,50% also decrease below 30%. The most frequent optimum solutions are vertical blinds 75%-60o.